2017
DOI: 10.1007/s00401-017-1782-y
|View full text |Cite
|
Sign up to set email alerts
|

Cofactors influence the biological properties of infectious recombinant prions

Abstract: Prion diseases are caused by a misfolding of the cellular prion protein (PrP) to a pathogenic isoform named PrP. Prions exist as strains, which are characterized by specific pathological and biochemical properties likely encoded in the three-dimensional structure of PrP. However, whether cofactors determine these different PrP conformations and how this relates to their specific biological properties is largely unknown. To understand how different cofactors modulate prion strain generation and selection, Prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
112
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(117 citation statements)
references
References 73 publications
5
112
0
Order By: Relevance
“…; Fernandez‐Borges et al . ). Two of the defining characteristics of prion strains are conformational stability (Safar et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Fernandez‐Borges et al . ). Two of the defining characteristics of prion strains are conformational stability (Safar et al .…”
Section: Discussionmentioning
confidence: 97%
“…Besides, previous studies had clearly shown that there is a dissociation between seeding ability and infectivity (Miller et al 2011;Barron et al 2016;Alibhai et al 2016;Groveman et al 2017), which means that the observed seeding capacity, similar in different groups of mice does not necessarily reflect that their levels of infectivity are also comparable. In the past, studies had described that the addition of cofactors could change the path of recombinant prions leading to the generation of different strains with relative infectious properties (Deleault et al 2012;Fernandez-Borges et al 2018). Two of the defining characteristics of prion strains are conformational stability (Safar et al 1998) and selective neurotropism (Bruce et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The in vitro prion replication and PrP res detection of amplified samples was performed as described previously with minor modifications . Briefly, brains used for substrate were perfused using PBS + 5 mM EDTA and the blood‐depleted brains were frozen immediately until required for preparing the 10% brain homogenates (PBS + NaCl 0.15 M + 1% Triton X‐100).…”
Section: Methodsmentioning
confidence: 99%
“…The in vitro prion replication and PrP res detection of amplified samples was performed as described previously with minor modifications. 51 Briefly, brains used for substrate were perfused using PBS + 5 mM EDTA and the blood-depleted brains were frozen immediately until required for preparing the 10% brain homogenates (PBS + NaCl 0.15 M + 1% Triton X-100). Brain homogenates (50-60 μL of 10%), either unseeded or seeded with the corresponding prion isolate/strain, were loaded into 0.2-mL of PCR tubes and placed into a sonicating water bath at 37-38°C without shaking.…”
Section: Generation Of In Vitro Prp Res By Serial Pmcamentioning
confidence: 99%
“…While the exact mechanism of prion replication remains unknown, cofactor molecules and PrP C glycosylation are both thought to play important roles in maintaining the biological infectivity [10][11][12][13][14][15] and strain properties of mammalian prions [16][17][18][19][20][21]. Using the serial protein misfolding cyclic amplification (sPMCA) technique [22,23], Nishina et al discovered that PrP C glycosylation preferences for prion propagation in vitro appear to be species-dependent [24].…”
Section: Introductionmentioning
confidence: 99%